English Learning in Primary School 2 Kenteng Nogosari (Ethnographic Research at SD Negeri 2 Kenteng Nogosari) - Palupi, Rismaka; Sujito, Sujito (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The study aims to gain a deep and comprehensive understanding of the English learning process of students of Grade II SD N 2 Kenteng Nogosari using ethnographic method in a qualitative approach. This process includes the roles of teachers and learners. Teachers can create a good learning atmosphere, have a positive impact on students' learning and achieve optimal learning outcomes. She is also the director of individual and group activities. Learners will always feel safe because teachers care about their students throughout the independent learning process. This approach is based on assumptions about the nature of language and how language learning occurs. Learning English is about developing contextual skills and acceptable English. It depends on the context, conditions and everyday circumstances of the learner. We recommend integrating research findings into popular teaching materials that are appropriate to the needs of students